Distributive justice and equity in transportation - Pereira, R; Schwanen, T; Banister, D (Taylor and Francis, 2016)
Over the past decades, transport researchers and policymakers have devoted increasing attention to questions about justice and equity. Nonetheless, there is still little engagement with theories in political philosophy to frame what justice means in the context of transport policies. This paper reviews key theories of justice (utilitarianism, libertarianism, intuitionism, Rawls’ egalitarianism, and Capability Approaches), and critically evaluates the insights they generate when applied to transport. Based on a dialogue between Rawlsian and Capability Approaches, we propose that distributive justice concerns over transport disadvantage and social exclusion should focus primarily on accessibility as a human capability. This means that, in policy evaluation, a detailed analysis of distributional effects of transport policies should consider minimum standards of accessibility to key destinations and the extent of which these policies respect individuals’ rights and prioritize disadvantaged groups, reduce inequalities of opportunities and mitigate transport externalities. A full account of justice in transportation requires a more complete understanding of accessibility than traditional approaches have been able to deliver to date.